PENGARUH STRES KERJA PADA KINERJA KARYAWAN DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL PEMODERASI - Rahardjo, Kenny Sundoro; Dewi, I Gusti Ayu Manuati (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 10 Nomor 2 Tahun 2016DO - 10.24843/MATRIK:JMBK.2016.v10.i02.p03, 2016)
The aim of this study is to examine the effect of work stress on employee performance with locus of control (LoC) as moderating variable. This research was conducted at Hotel Novotel Bali Benoa with 73 employees as sample. Samplingtechnique used was probability sampling, especially proportionate stratified random sampling. Data were collected through questionnaire containing 24 indicators of job stress, LoC, and employee performance. Data analysis technique implemented was Moderated Regression Analysis. The findings show that work stress is negatively affect employee performance. Locus of control has significant effect on the performance of the employees. In contrast to expectation, internal LoC has negative effect employee performance. Additionally, LoC emerges as moderating variable at the effect of work stress on employee performance
Keywords: work stress, locus of control, employee performance